Creative Leadership in Digital Startups: A Longitudinal Case Study in Innovation Management - Sulistyorini Sulistyorini; Roya Zahir; Zara Ali (Journal of Loomingulisus ja Innovatsioon, 2025)
In the hyper-competitive digital economy, the survival and growth of startups are intrinsically linked to their capacity for continuous innovation. While leadership is acknowledged as a critical driver of innovation, there is a limited understanding of how creative leadership specifically manifests and evolves over time within the volatile startup environment. This study aims to address this gap by longitudinally exploring the dynamics of creative leadership and its influence on innovation management processes within a digital startup. It seeks to identify the key leadership behaviors that foster a sustainable innovation culture and to understand how these behaviors adapt to the startup’s developmental stages. Employing a qualitative longitudinal case study approach, this research tracked a single digital startup over a three-year period. Data were collected through semi-structured interviews with the founding team and employees, direct observation of team meetings, and an analysis of internal documents related to project development and strategic planning. Key practices identified include fostering psychological safety, championing nascent ideas, and strategically allocating resources for experimentation. These leadership practices directly correlated with the development of an agile and resilient innovation management system. The study concludes that effective creative leadership in digital startups is contingent on the leader’s ability to adapt their style to the organization’s evolving needs.